Practical Aspects Of Approval Of Accounting In Equity Companies - Joraev Dilmurod Kholmo'minovich (Academia One, 2024)
In this article, it serves to form the regulatory legal documents on accounting, accounting documents, accounting transfers, and reporting data for the preparation of financial statements in the preparation of financial statements of joint-stock companies based on international standards.
Keywords: Joint-stock companies; international standards of accounting; accounting system